1992
DOI: 10.1111/j.1471-0528.1992.tb14438.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of serial biophysical assessment of fetal wellbeing in gastroschisis

Abstract: Objective To review antenatal and intrapartum assessment of pregnancies complicated by gastroschisis. Design Retrospective descriptive study. Setting University College Hospital, London. Subjects 24 consecutive cases of gastroschisis between 1986 and 1991. Results The gestational age at sonographic diagnosis was 20.3 weeks (SD 6.77) and at birth was 36.5 weeks (SD 2.06). There were 21 live births, all with good surgical outcome. There were 16 vaginal deliveries and eight caesarean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
62
1
19

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 17 publications
13
62
1
19
Order By: Relevance
“…Patients who underwent a CS for fetal distress had a higher rate of induction of labor and their infants had a lower birth weight compared with women that underwent vaginal delivery. Fries et al 10 and Crawford et al 6 showed that fetuses with lower birth weights had a trend toward an increased rate of CS. In an attempt to analyze the characteristics of fetal distress in fetuses with gastroschisis, Ingamells et al 9 analyzed the computerized cardiotocography findings in 18 fetuses with gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients who underwent a CS for fetal distress had a higher rate of induction of labor and their infants had a lower birth weight compared with women that underwent vaginal delivery. Fries et al 10 and Crawford et al 6 showed that fetuses with lower birth weights had a trend toward an increased rate of CS. In an attempt to analyze the characteristics of fetal distress in fetuses with gastroschisis, Ingamells et al 9 analyzed the computerized cardiotocography findings in 18 fetuses with gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
“…These were attributed to hypoxemia. Crawford et al 6 reported baseline tachycardia as the typical abnormality in the fetal heart rate. The observation of an increased incidence of fetal distress is indirectly supported by the high rate of unexplained intrauterine deaths and stillbirths in fetuses with gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations